HUBUNGAN BODY SHAMING DENGAN TINGKAT STRESS PADA MAHASISWA - Putri, Dhea Eka (Jurnal Keperawatan Profesional, 2024)
Body shaming is a form of verbal bullying that involves judging and commenting on someone's physical appearance deemed less than ideal, causing feelings of shame. Persistent experiences of body shaming can lead to various psychological issues such as emotional disturbances, social withdrawal, and stress. Prolonged stress resulting from body shaming can lead to more serious mental disorders. This research aims to investigate the relationship between body shaming and stress levels among university students. The study employs a quantitative design with a cross-sectional approach. The research sample consists of 206 respondents selected based on inclusion criteria using quota sampling technique. Measurement tools include the Body Shaming questionnaire and DASS-42. Data is analyzed using univariate and bivariate analysis with the Chi-Square test at a significance level of α 0.05. Results indicate that 108 respondents (52.4%) experience moderate levels of body shaming, and among them, 71 also experience moderate stress levels. Overall, it can be concluded that there is a significant relationship between body shaming and stress levels among university students (p-value 0.004). Students are encouraged to raise awareness about stress resulting from experiencing body shaming and to reduce the occurrence of body shaming to alleviate stress levels. Further research, conducted offline, can explore the direct impacts of stress due to body shaming on university students.